1998
DOI: 10.1007/s11746-998-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing short‐chain fatty acid yield during lipase hydrolysis of a butterfat fraction with periodic aqueous extraction

Abstract: Factors affecting the release of short-chain fatty acids during hydrolysis of a butterfat fraction with a 1,3-positional and short-chain-specific Penicillium roqueforti lipase were investigated. When a short-chain triglyceride fraction was used as substrate, as opposed to whole butterfat, the ratio of desirable flavor short-chain free fatty acids (FFA) to undesirable medium-chain FFA in the FFA fraction increased from 0.75 to 1.80. However, with both substrates, FFA accumulation eventually led to lipase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…(1992) reported that FFA decreased the hydrolytic activity of P. cepacia lipase in olive oil. Similar results are reported by Lenki et al. (1998) for the hydrolysis of butterfat fraction.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…(1992) reported that FFA decreased the hydrolytic activity of P. cepacia lipase in olive oil. Similar results are reported by Lenki et al. (1998) for the hydrolysis of butterfat fraction.…”
Section: Resultssupporting
confidence: 90%
“…Dunhaupt et al (1992) reported that FFA decreased the hydrolytic activity of P. cepacia lipase in olive oil. Similar results are reported by Lenki et al (1998) for the hydrolysis of butterfat fraction. Table 2 shows the effect of water content on the percentage of FFA produced during the hydrolysis process at 50C by lipase from C. rugosa.…”
Section: Hydrolysis Processsupporting
confidence: 90%
“…It is well known that the hydrolysis of milk fat triacylglycerols by lipases releases short‐chain fatty acids that are correlated with the unpleasant flavor of dairy products (Lenckia et al, ). FFA content of the raw milk used in this experiment was relatively high; 0.54 g 100‐g −1 , which indicates poor quality milk used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The SCFA were mostly released from the hydrolysis of TAG from milk fat, the flavor thresholds of which were low, indicating that the amount and composition of SCFA have a significant influence on the quality of milk flavor. Among them, butyric acid and caproic acid were the key flavor components in milk, which affect milk flavor when present in normal concentrations (Lencki et al, 1998;Biolatto et al, 2007). Caprylic acid and capric acid, having oily and waxy aromas, were also typical substances affecting milk flavor.…”
Section: Analysis Of Volatiles Of the Recombined Milk Products By Hs-mentioning
confidence: 99%